Rearrangements of 2-Pyridyl-3-arylaminoisoxazol-5(2H)-ones to Imidazo[1,2-a]pyridines under Flash-Vacuum-Pyrolysis - Setamdideh, Davood; Khanahmadzadeh, Salah; Khorshidi, Nasrin (Asian Journal of Chemistry, 2012)
2-Pyridyl-3-arylaminoisoxazol-5(2H)-ones, rearranged under flash-vacuum-pyrolysis (FVP) conditions accompanied by elimination of carbon dioxide to give imidazo[1,2-a]pyridines in high to excellent yields (85-95 %).